The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.21608/jssae.2019.79683
|View full text |Cite
|
Sign up to set email alerts
|

Soil Physicochemical Properties, Water Use Efficiency and Productivity of Wheat - Maize Yields under Clay Soil Conditions as Affected by Rice Straw and Compost Application

Abstract: Two field experiments were implemented at El-Gemmieza Agric., Res. Station, Agric., Res., Center in El Gharbiah Governorate, Egypt through (2017/2018) seasons to investigate the impact of rice straw and compost application on soil physicochemical properties, water use efficiency and production of both wheat and maize yields. The design of experiment was complete randomized blocks design with three replicates, the experiment comprises the following treatments: T 1 : (control), T 2 : 2.50 t ha -1 (RS), T 3 : 5.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…In another study on residue return, it has been shown that the effect of residues on potato WUE depends on soil fertility, temperature, and inorganic fertilization conditions (Li et al, 2018) [34] . The study conducted on impact of rice straw compost reported that the WUE and the productivity of grains of wheat and maize (Mgm -3 ) acquired from every cubic meter water in each seasons (2017/2018) were improved (El-Gamal et al, 2019) [16] as indicated in Table 1. The values for WUE ranged between 1.73 and 1.90 Mgm -3 for the wheat crop while it ranged between 1.15 and 1.46 Mgm -3 for maize crop.…”
Section: Water Use Efficiencymentioning
confidence: 99%
“…In another study on residue return, it has been shown that the effect of residues on potato WUE depends on soil fertility, temperature, and inorganic fertilization conditions (Li et al, 2018) [34] . The study conducted on impact of rice straw compost reported that the WUE and the productivity of grains of wheat and maize (Mgm -3 ) acquired from every cubic meter water in each seasons (2017/2018) were improved (El-Gamal et al, 2019) [16] as indicated in Table 1. The values for WUE ranged between 1.73 and 1.90 Mgm -3 for the wheat crop while it ranged between 1.15 and 1.46 Mgm -3 for maize crop.…”
Section: Water Use Efficiencymentioning
confidence: 99%